Analisis Sinergitas Kantor Pencarian dan Pertolongan Yogyakarta dengan Relawan di Kabupaten Sleman dalam Respons Bencana Gunung Merapi - Br Tarigan, Eliasna; Katon Mahendra, Gerry (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
Indonesia is located at the confluence of three major tectonic plates, making it highly prone to disasters. Sleman Regency in the Special Province of Yogyakarta faces seven potential disasters, including Mount Merapi eruptions, which demand strong synergy between the Yogyakarta Search and Rescue Office and local volunteers. However, suboptimal coordination, limited resources, and procedural differences remain major obstacles to effective disaster response. This study aims to analyze the synergy between the Yogyakarta Search and Rescue Office and the volunteer network in Northern Sleman based on five key indicators: communication, rapid feedback, trust, coordination, and creativity. A descriptive qualitative method was employed using the Miles and Huberman analysis model. Results show that communication is effective through various media, despite network constraints in certain areas. Rapid feedback is reflected in the National Search and Rescue Agency's prompt response to verified volunteer reports. Trust is built through shared experiences, competency certification, and mutual recognition of technical capabilities. Coordination operates within a joint command post structure with a clear division of tasks, though not all volunteers are familiar with standard operating procedures (SOPs). Meanwhile, volunteers' creativity plays a crucial role in developing local solutions, such as utilizing simple tools and alternative routes. Key challenges include communication barriers, limited equipment and human resources, and gaps in SOP comprehension. Overall, synergy between the two parties has been reasonably strong, though it requires further reinforcement through joint training, integrated SOPs, and regular evaluation forums to ensure a faster, more adaptive, and more effective response to Merapi disasters.